PENINGKATAN MINAT SISWA BERMAIN MUSIK SARUNAI DENGAN METODE DEMONSTRASI DI SMA NEGERI 5 SOLOK SELATAN KECAMATAN KOTO PARIK GADANG DI ATEH - Firmon Firmon; Ardipal Ardipal; Yos Sudarman (FBS Universitas Negeri Padang, 2013)
Abstract The background of this research is based on the low of the students, interest play sarunai. Specially to the students of grade X in SMAN 5 South solok. The goal of this research is to reveal that the using of demonstrasion can increase the students, interest in playing sarunai in grade X-1 in SMAN 5 South Solok. The benefit of this research is as the input for the art and culture teacher especially in SMAN 5 South Solok in increasing the interest of students in learning play sarunai.This research is class action research that in done by using the model of cycle that divided into 4 steps that is planning, action, observation, and reflection. The sample of this research is the students of grade X-1 SMAN South Solok semester 2 january-june 2013 with 30 students. The instrument that is used is observation sheet as tally list. That contents of analyzed by using the percentage formula P= (F/N) X 100%.The result of the research shows that there is the increasing of the students, interest in playing sarunai in cycle 1 is 54,6 % and in the 2 is 81,9 % it means there is the increasing the students interest to play sarunai by using demonstrasion method from the cycle 1 to cycle 2 is 27,3 %. Key words: the increasing of students, intereset play sarunai music by the demonstration method.